Removal of Pesticide Residues from Tomato and its Products - Aasia Akbar Panhwar,; Saghir Ahmed Sheikh,; Aijaz Hussain Soomro,; Ghulam Hussain Abro, (Journal of Basic & Applied Sciences, 2014)
Plant protection agents (more commonly known as pesticides) are widely used in agriculture to increase the yield, improve the quality and extend the storage life of food crops. The study was carried out in order to determine the effectiveness of various traditional processing treatments on reducing the residual load of pesticides from tomato and its products. Results showed that lipid soluble pesticides residues were reduced most effectively in sun-drying (90-97%) followed by frying (91-99%) and thermal dehydration (89-90%). The data further indicated that profenofos residues dislodged more effectively than bifenthrin and endosulfan. The least reduction was noticed in endosulfan residues. Similarly in case of water soluble pesticides, the effect of sun-drying, frying and thermal dehydration on reduction of pesticide residues were within the range of 94-97%, 92-96% and 91-96%, respectively. Maximum reduction was found in emamectin benzoate residues followed by imidacloprid and diafenthiuron.